Understanding corporate governance: how it affects company performance at Ferrotec Manufacturing Malaysia Sdn. Bhd. - Mohamed Shaiful Azam, Nur Fatini (2025)
Corporate governance refers to the system by which companies are directed, controlled, and held accountable. Corporate governance plays a pivotal role in shaping the operational effectiveness and long-term sustainability of organizations. This study explores the impact of corporate governance on the performance of Ferrotec Manufacturing Malaysia Sdn. Bhd., a leading player in the manufacturing sector. By analyzing the governance structure, decision-making processes, and internal controls at Ferrotec, the research aims to assess how these factors influence company performance in terms of profitability, productivity, and market competitiveness. The study employs a qualitative approach, utilizing case studies, interviews with key stakeholders, and analysis of company reports to examine the relationship between governance practices and organizational outcomes. The findings suggest that effective corporate governance contributes to improved financial performance, risk management, and strategic alignment within the company. Additionally, the study identifies key areas for improvement in governance practices that could further enhance Ferrotec’s operational success. The research offers valuable insights for both scholars and practitioners interested in understanding the dynamics between corporate governance and business performance in the context of a Malaysian manufacturing firm.